Influence of Human, Livestock Population and Land use Systems on Soil Characteristics and Soil Organic Carbon Stock in Western Rajasthan - Singh, G; Nagora, P R; Mishara, Deepak; Hakasr, Parul; Gola, Sneha; Dandapath, Taipy (Annals of Arid Zone, 2019)
A study has been conducted during 2016-17 to estimate soil organic carbonstock in 0-30 cm soil depth as influenced by land use, spatial variations and human andlivestock population for developing strategies to reduce land degradation and enhancecarbon sequestration and land productivity. Forests, oran, pasture lands, agriculture,roadside and fallow land are different land uses covered in six Panchayat Samitis-calledblocks viz. Abu Road, Baap, Baitu, Bali, Sanchor and Sankara situated in Sirohi, Jodhpur,Barmer, Pali, Jalore and Jaisalmer district, respectively in western Rajasthan. Landholding (2444-37444 m2), family size and livestock population in terms of head countsper household (HH-1; 5.3-5.9 and 4.4-11.0, respectively) varied (P